2019
DOI: 10.1093/mnras/stz754
|View full text |Cite
|
Sign up to set email alerts
|

Stellar spectral models compared with empirical data

Abstract: The empirical MILES stellar library is used to test the accuracy of three different, state-of-theart, theoretical model libraries of stellar spectra. These models are widely used in the literature for stellar population analysis. A differential approach is used so that responses to elemental abundance changes are tested rather than absolute levels of the theoretical spectra. First we directly compare model line strengths and spectra to empirical data to investigate trends. Then we test how well line strengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 63 publications
7
29
0
Order By: Relevance
“…7, 8 and 11 show a complex and index-dependent behaviour. One may argue that the best performance of the sps-s models occurs for the indices H10, B4000, Hδ F , CN 2 , G4300, Hγ F , Fe4383, Hβ, Mg b and Fe5782, whereas the indices that deserve most attention from modellers are Fe5270, Fe5015, CaHK, Fe5709, Fe4383 and Fe4668 (the latter had already been pointed out by Knowles et al 2019).…”
Section: How Do Uncertainties In Theoretical Stellar Libraries Affectmentioning
confidence: 94%
See 2 more Smart Citations
“…7, 8 and 11 show a complex and index-dependent behaviour. One may argue that the best performance of the sps-s models occurs for the indices H10, B4000, Hδ F , CN 2 , G4300, Hγ F , Fe4383, Hβ, Mg b and Fe5782, whereas the indices that deserve most attention from modellers are Fe5270, Fe5015, CaHK, Fe5709, Fe4383 and Fe4668 (the latter had already been pointed out by Knowles et al 2019).…”
Section: How Do Uncertainties In Theoretical Stellar Libraries Affectmentioning
confidence: 94%
“…(iii) Synthetic stellar spectra were computed with the SYNTHE code (Kurucz & Avrett 1981;Sbordone et al 2004), based on the ATLAS9 and MARCS models. The opacities are as in C14 with one update, the inclusion of the molecular transition C 2 D-A from Brooke et al (2013) 6 to correct for the problem identified by Knowles et al (2019). For stars with T eff ≥ 3500 K the synthetic spectrum was computed based on the ATLAS9 models.…”
Section: Syncomil: a Synthetic Counterpart To The Miles Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…This approach, making use of both models and observations, builds upon the work of La Barbera et al (2017), implementing both the accuracy of empirical spectra with the differential abundance pattern predictions of theoretical spectra. Using only differential predictions from theoretical spectra has been shown to reproduce observations of abundance pattern effects more accurately than fully theoretical spectra, particularly for wavelengths below Mg b (e.g see figure 11 of Knowles et al 2019or Martins & Coelho 2007Bertone et al 2008;Coelho 2014;Villaume et al 2017;Allende Prieto et al 2018).…”
Section: Models Of Stellar Spectramentioning
confidence: 99%
“…In this subsection, we compare the performance of Spectra-GANs, PCA, DnCNN, RBM, and Wavelet on recovering the Lick index. The Lick/IDS index system is a set of absorption-line indices, defined by the Lick group for low-resolution (R∼8) spectra with wavelength coverage between the range of 4000Å and 6400Å [34]- [39], which is often used as an approach to measure the atmospheric parameters in stars and galaxies. Barbuy et al explored In this experiment, we first denoised the spectra with Spectra-GANs, PCA, DnCNN, RBM, and Wavelet, and then computed the Lick indices of the denoised spectra.…”
Section: B Quantitative Comparisonmentioning
confidence: 99%